Biomass burning-agriculture coupling in the Orinoco savannas—Particulate matter emission scenarios - Jimenez, Rodrigo; Ardila, Andres V.; Vargas-Burbano, Angela C.; Hernandez, Andrea J.; Leon-Velasquez, Elizabeth (Frontiers in Environmental Science, 2022)
The Colombian Orinoco savannas (254 thousand km2), also known as Orinoquia or Llanos, have been steadily transformed into pastures for more than a century, and since the 1990s, into commodity crop intensified production. The cropland area expanded at 12% yr-1 during the 2007-2018 period (65% larger than in 1996-2007). Yet, we estimate that cattle ranching occupied ten times more area (34%) than cropland (3.2%) in 2018. The rest of Orinoquia, including indigenous reservations and protected areas, was in a semi-natural state, although also exposed to seasonal fire. The three main crops, oil palm, corn, and rice (72% of the sown area in 2017), accounted for 68% of the expansion, with permanent crops expanding two times faster (18% yr-1) than short-cycle crops. An extrapolation of trends indicates that the cultivated area will double by 2040 (reaching 20 thousand km2), with oil palm as the dominant crop. Satellite measurements show that 7% of Orinoquia burned every year during the 1997-2016 period, yet with large spatial and interannual variations (±26%), and significant decrease trends (up to -4% yr-1). Up to 40% of the burned area (BA) interannual variability was linked to irregular rainfall and drought. The areas with the larger fractional BA were also those with the least fractional cropland cover. A model developed to describe this coupling, along with rainfall and other effects, successfully explained most of Orinoquia’s BA variability (r2 = 0.93). The fitted model indicates that each sown hectare reduced the BA by 0.17 ha. This model predicts that the combination of cropland expansion and independent BA decline will lead to a fourfold reduction of Orinoquia’s BA by 2040 referred to 1997. Orinoquia’s crop production generated 3 Gg of PM10 (particulate matter < 10 µm) in 2016, mostly from short-cycle crops, while biomass burning generated 57 Gg, i.e., 95% of the combined emissions. These are expected to halve during the 2017-2040 period, despite an 83% increase in crop production emissions, as total and seasonal emissions will remain controlled by biomass burning. Such a large pollution burden reduction should have tremendous positive impacts on public health in Orinoquia and the Andes.